Effect of Service Period, Gestation Period and Dry Period on Milk Production Traits in Kankrej Cattle - Pareek, Nawal Kishor; Ankuya, K.J.; Patel, M.P.; Rathod, B.S.; Prajapati , K.B. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
The present investigation was undertaken to study the effect of non-genetic factors, viz., service period (SP), dry period (DP) and gestation period (GP) on various milk production traits in Kankrej cattle. 1235 lactation records (2nd-7th ) of 475 Kankrej cows, progeny of 75 bulls that were maintained at University Livestock Research Station, Sardarkrushinagar (Gujarat), calved during 1980-2014, were studied. The effects of service period (111.64 ± 52.55 days) and dry period (143.17±28.78 days) on total lactation milk yield (2089.45±582.38 kg),305 days milk yield (2045.66±531.92 kg) and lactation length (282.90±49.46 days) were highly significant (p<0.01 ), while the effect of gestation period (288.86±7.14 days) was non-significant on all these production traits. Cows which took more time to conceive after parturition produced more milk with longer lactation length.